2016
DOI: 10.1038/ncomms12652
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor controls cyclin O to promote epithelial multiciliogenesis

Abstract: Epithelia function as barriers against environmental insults and express the transcription factor aryl hydrocarbon receptor (AhR). However, AhR function in these tissues is unknown. Here we show that AhR regulates multiciliogenesis in both murine airway epithelia and in Xenopus laevis epidermis. In air-exposed airway epithelia, induction of factors required for multiciliogenesis, including cyclin O (Ccno) and Multicilin (Mcidas), is AhR dependent, and air exposure induces AhR binding to the Ccno promoter. Subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Interestingly, Irf7 −/− and Ifnar2 −/− (deficient for type I IFN receptor) mice displayed normal dendritic cell development and allergic airway sensitization in response to HDM 81 , suggesting independence between type I IFN signaling and HDM-induced airway allergy when Tet1 is present. On the other hand, the AhR pathway, the second most significantly enriched pathway in our analysis, regulates airway epithelial multiciliogenesis 93 and oxidative stress responses 60 , and contributes to asthma development and exacerbation 46,62,94 . Specifically, AhR ligands attenuate allergic airway inflammation in OVA-challenged animal models 94,95 , suggesting that down-regulation of the AhR pathway by Tet1 would increase the severity of HDM-induced allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, Irf7 −/− and Ifnar2 −/− (deficient for type I IFN receptor) mice displayed normal dendritic cell development and allergic airway sensitization in response to HDM 81 , suggesting independence between type I IFN signaling and HDM-induced airway allergy when Tet1 is present. On the other hand, the AhR pathway, the second most significantly enriched pathway in our analysis, regulates airway epithelial multiciliogenesis 93 and oxidative stress responses 60 , and contributes to asthma development and exacerbation 46,62,94 . Specifically, AhR ligands attenuate allergic airway inflammation in OVA-challenged animal models 94,95 , suggesting that down-regulation of the AhR pathway by Tet1 would increase the severity of HDM-induced allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies mainly demonstrated various mutations and important functions in respiratory disease. 13 , 22 , 23 However, studies concerning the role of CCNO in cancer are rarely reported. Therefore, the clinical significance and functional role of CCNO in human cancer, including GC, remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Polyaromatic hydrocarbon levels are increased in the plasma of asthmatic children and linked to a number of asthma markers 98 . The aryl hydrocarbon receptor (AhR), which plays a key role in detoxification of environmental pollutants, also regulates multiciliogenesis 99 . Importantly, although air exposure triggers AhR targeting of genes important for multiciliogenesis, toxic AhR ligands induce detoxifying cytochromes, with no overlap in target gene induction.…”
Section: Dysregulation Of the Epithelial Barrier In Asthmatic Patientsmentioning
confidence: 99%